Differences in seasonal best times between short and long course in freestyle events in Spanish age-group swimmers - Hermosilla, Francisco; Beltrán-Díaz, Emilio; Tomohiro, Gonjo; Juárez Santos-García, Daniel (My University, 2023)
Swimmers perform better times in short course due to the greater numbers of turns; however, the differences between short (SC) and long course (LC) depending on the swimmers¿ age and sex are unclear. The main aim of this study was to analyse the differences in seasonal best times between SC and LC in freestyle events in relation to age and sex. Seasonal best times performed in SC and LC in each freestyle swimming event of 100 top national Spanish swimmers in two seasons were included in this analysis. A three-way ANOVA was performed to analyse the effect of the three factors on the difference between SC and LC times. Senior swimmers presented the greatest differences between SC and LC in comparison with other age-groups. Age-groups 11¿12 and 14¿16 showed similar SC and LC differences; nevertheless, these differences are significant (p¿<¿0.05) with the 13¿14 age-group. Generally, from 14 to 15¿years old the differences between SC and LC increased. The result of this study indicates that the differences between SC and LC are unsteady throughout the swimming career. Thus, when considering swimmers¿ performance using both SC and LC results, SC results should be adjusted depending on the age of the swimmers.